Exploring association between self-reported financial status and economic preferences using experimental data - Calvin Mudzingiri; Sevias Guvuriro; Charity Gomo (Journal of Risk and Financial Management, 2021)
Research on economic behaviour of individuals in different financial statuses such as being in a good financial standing or in a threatening financial situation are inconclusive. Some evidence suggest that the culture of poverty may shape and dominate the economic preferences of those who are poor and even make them being prone to trembling and making mistakes thereby making decisions that do not maximize their utility. Other evidence suggest that the poor exercise extra caution and fail to maximize utility. This study investigates the association between self-reported financial status and economic preferences in a developing country setting using data from an incentivized experiment and a survey. Extended random effects panel probit regression models are employed as an analytical strategy. The study established a positive association between being financially broke or very broke and being risk averse. In addition, a positive association is found between being financially "very broke" and impatient. Such findings illustrate the importance of psychology of poverty in economic preferences and in decision-making in general, even as poverty is temporary as represented by self-reported financial status.
Keywords: 330; culture of poverty; financial decision-making; financial status; financially very broke; risk preferences; time preferences